The relationship between optimism, pessimism and sleep difficulties in university students: The role of cognitive emotion regulation and psychological distress - Afonso,Boaventura R. C. R. O. (2024)
Abstract We found that the factors involved in the genesis/maintenance of sleep difficulties needed to be much better known. Our aims were to explore the role of cognitive emotion regulation (CER) and psychological distress (PD) as mediators in the relationship between pessimism/optimism and sleep difficulties. Our methods were to ask 253 university students to complete the Depression, Anxiety and Stress Scale-21, the Optimism-Pessimism-2 Scale, the Cognitive Emotion Regulation Questionnaire (CERQ), and answer three questions about sleep difficulties. Our results showed that optimism, adaptive/positive CER strategies, positive reappraisal and refocusing on planning (CERQ1) correlated inversely with sleep difficulties, whereas pessimism, PD, and non-adaptive/negative CER strategies correlated positively with them. Pessimism was a vulnerability factor for sleep difficulties, with its indirect effect mediated by negative CER and/or increased PD. Optimism had a protective effect against sleep difficulties through CERQ1 and/or the reduction of PD. Our conclusion was that fostering adaptive CER strategies, reducing non-adaptive strategies, and addressing pessimism may have clinical implications for promoting psychological well-being and improving sleep quality.